Dark fermentation production of volatile fatty acids from glucose with biochar amended biological consortium. (May 2020) - Lu, Jia-Hsun; Chen, Chuan; Huang, Chihpin; Zhuang, Huichuan; Leu, Shao-Yuan; Lee, Duu-Jong
Highlights: Nine biochars were synthesized and added into fermentation broth of glucose. Adding biochars or activated carbon produce preferably acetate over butyrate. Biochar coconut and biochar longan shell preferred mostly on acetate production. Syntrophic growth of fermentative bacteria and homoacetogens promotes reaction. Abstract: Effects of adding biochars on dark fermentation production of volatile fatty acids (VFAs) from glucose were investigated. Nine biochars were synthesized and applied, together with an activated carbon, as the testing amendment to enhance preferable fermentation. Biochars were porous materials with internal pores and excess surface functional groups, which would lead to enrichment of acetate over butyrate in the VFA production. Biochar coconut and biochar longan shell showed excess functional groups and high bulk internal crystallinity, presented 109.6% and 71.8% enrichments of acetate production, respectively. The syntrophic growth of fermentative bacteria and homoacetogens on biochar surfaces via direct interspecies electron transfer mechanism was assumed to interpret the noted enhanced acetate production. The excess functional groups on biochar surface to facilitate biofilm development and the high crystallinity of biochar bulk to ease electron transfer favored the production of acetate.